2022
DOI: 10.1089/jop.2021.0099
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Open-Angle Glaucoma and Ocular Hypertension with Preservative-Free Tafluprost/Timolol Fixed-Dose Combination Therapy: Results from the VISIONARY Study Population in Spain

Abstract: Purpose: Data are presented from ophthalmology clinics in Spain participating in the VISIONARY study, examining the effectiveness, tolerability, and safety of the preservative-free tafluprost (0.0015%) and timolol (0.5%) fixed-dose combination (PF tafluprost/timolol FC) in the treatment of OAG and OHT. Methods: An observational, multicenter prospective study examined treatment outcomes following a switch to PF tafluprost/timolol FC in adult OAG/OHT patients demonstratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…This study also found that the EDV and PSV levels of the CRA and the SPCA were signi cantly increased and the RI level of the CRA and the SPCA were signi cantly decreased after treatment in both groups. In addition, the improvement of the above indexes in the observation group is more remarkable, which indicates that Ta uprost has a better effect on ocular hemodynamics in patients with primary open-angle glaucoma, which is consistent with previous studies.. VEGF drugs are widely used in the treatment of neovascular glaucoma, for example trabeculectomy combined with conbercept or ranibizumab in the treatment of neovascular glaucoma (NVG) can make new blood vessels regress, effectively control IOP and improve vision, and the e cacy of the above treatment was achieved through the regulation of VEGF [18][19]. In addition, postoperative application of brinzolamide combined with timolol eye drops in the treatment of NVG patients can effectively reduce IOP and control its uctuations, and these effects are mainly achieved by regulating the balance of angiogenesis promoting/inhibiting factors, VEGF and its receptors.…”
Section: Analysis Of Clinical Effect Of Ta Uprost On Patients With Pr...supporting
confidence: 86%
“…This study also found that the EDV and PSV levels of the CRA and the SPCA were signi cantly increased and the RI level of the CRA and the SPCA were signi cantly decreased after treatment in both groups. In addition, the improvement of the above indexes in the observation group is more remarkable, which indicates that Ta uprost has a better effect on ocular hemodynamics in patients with primary open-angle glaucoma, which is consistent with previous studies.. VEGF drugs are widely used in the treatment of neovascular glaucoma, for example trabeculectomy combined with conbercept or ranibizumab in the treatment of neovascular glaucoma (NVG) can make new blood vessels regress, effectively control IOP and improve vision, and the e cacy of the above treatment was achieved through the regulation of VEGF [18][19]. In addition, postoperative application of brinzolamide combined with timolol eye drops in the treatment of NVG patients can effectively reduce IOP and control its uctuations, and these effects are mainly achieved by regulating the balance of angiogenesis promoting/inhibiting factors, VEGF and its receptors.…”
Section: Analysis Of Clinical Effect Of Ta Uprost On Patients With Pr...supporting
confidence: 86%
“…These data are reflective of the primary VISIONARY publication and of other real-world data concerning IOP-lowering efficacy with PF tafluprost/timolol FC following a switch away from different topical glaucoma medications [ 22 , 23 ]. Emerging country-level data from the VISIONARY study has revealed differences in baseline IOP, with clinicians in some countries selecting patients with higher IOPs for inclusion in the study [ 31 – 34 ]. As pre-treatment pressure is predictive of IOP change, it is likely that these differences may have influenced the IOP reductions observed in the full Europe-wide dataset, and further subanalysis of these data according to country would be of value [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“… 45 Indeed, the relative change in IOP at Month 6 observed in the Italian dataset was slightly greater than the reductions published for Hungary and was similar to those for the UK and Spain where the starting IOP was marginally higher. 41 , 42 , 44 At Month 6, the majority of the Italian ophthalmologists considered PF tafluprost/timolol FC to be associated with better IOP control (78.8%), compared with previous monotherapy, and this is likely to have been supported by the reassuringly high levels of treatment compliance observed by investigators during this real-world study. Change in IOP was significant, regardless of whether patients instilled their medication in the morning or evening.…”
Section: Discussionmentioning
confidence: 67%